Methyl ester and aromatic ether modification of mitragynine for generation of mitragynine-specific polyclonal antibodies - Mustafa, Radhiahtul Raehan; Sukor, Rashidah; Mohd Nor, Siti Mariam; Saari, Nazamid (Elsevier, 2022)
Mitragynine is an alkaloid from Mitragyna speciosa Korth. (kratom), a native tropical plant in Southeast Asia. It could render psychotropic effects and is often misused in substitution for commercial drugs. In recent years, the consumption of kratom has grown rapidly and has led some countries to ban its use. The misuse of kratom can be detected and monitored through the determination of mitragynine from biological samples of the users. Therefore, the development of a rapid and effective detection method is needed. In this study, polyclonal antibodies were produced using mitragynine coupled to a carrier protein (cationic bovine serum albumin, cBSA) as an immunogen, which was prepared with coupling agents (i.e., N, N- dicyclohexylcarbodiimide, DCC and N-hydroxysuccinimide, NHS). It was conjugated to different mitragynine structure, 16-COOCH3 (methyl ester) and 9-OCH3 (aromatic ether). 2,4,6-Trinitrobenzenesulfonic acid (TNBS) method showed that 45 and 46 amino groups were bound to C22-MG-cBSA and C9-MG-cBSA, respectively. Fourier-transform infrared spectroscopy (FTIR) spectral changes at C22- and C9-hydroxymitragynine indicated reduction and demethylation process. In UV–Vis spectra, conjugated mitragynine to cBSA and OVA were displayed at a spectral region at 240–300 nm. For the antibody titre, the C22-MG-cBSA anti-serum showed a significantly higher titre than the C9-MG-cBSA at 1/128000 and 1/32000 dilutions, respectively. The detection range of the developed competitive indirect ELISA (CI-ELISA) was 0.01 to 10.00 μg/mL (R2 = 0.9964). The assay exhibited a limit of detection (LOD) and limit of quantification (LOQ) at 0.041 and 0.124 μg/mL, respectively. The antibody produced is a high-value biorecognition molecule that can be further used in developing immuno-based detection methods such as immunosensors and immunochromatographic lateral flow assays. This will benefit the task force or forensic agencies for toxicological screening with high speed and efficiency.